Single CD28 stimulation induces stable and polyclonal expansion of human regulatory T cells - He, Xuehui (Sci Rep, 2017)
CD4+FOXP3+ Treg are essential for immune tolerance. Phase-1 clinical trials of Treg-therapy to treat graft-versus-host-disease reported safety and potential therapeutic efficacy. Treg-based trials have started in organ-transplant patients. However, efficient ex vivo expansion of a stable Treg population remains a challenge and exploring novel ways for Treg expansion is a pre-requisite for successful immunotherapy. Based on the recent finding that CD28-signaling is crucial for survival and proliferation of mouse Treg, we studied single-CD28 stimulation of human Treg, without T cell receptor stimulation. Single-CD28 stimulation of human Treg in the presence of recombinant human IL-2(rhIL-2), as compared to CD3/CD28/rhIL-2 stimulation, led to higher expression levels of FOXP3. Although the single-CD28 expanded Treg population was equally suppressive to CD3/CD28 expanded Treg, pro-inflammatory cytokine (IL-17A/IFNγ) production was strongly inhibited, indicating that single-CD28 stimulation promotes Treg stability. As single-CD28 stimulation led to limited expansion rates, we examined a CD28-superagonist antibody and demonstrate a significant increased Treg expansion that was more efficient than standard anti-CD3/CD28-bead stimulation. CD28-superagonist stimulation drove both naïve and memory Treg proliferation. CD28-superagonist induction of stable Treg appeared both PI3K and mTOR dependent. Regarding efficient and stable expansion of Treg for adoptive Treg-based immunotherapy, application of CD28-superagonist stimulation is of interest.